TELAAH KONSEPTUAL TRANSFER PENGETAHUAN MELALUI KOLABORASI UNIVERSITAS DAN INDUSTRI - Lina Anatan (Akademi Akuntansi YKPN Yogyakarta, 2011)
This paper reviews the conceptual and empirical literatures concerned on knowledge transfer through university-industry collaboration. Resource- and knowledge-based theorists claim that firms should focus on the creation and accumulation of knowledge-based competencies in order to yield long-term survival. Firm’s knowledge can include technological knowledge as well as knowledge about how to function in global markets, work with local laws, how to protect intellectual property and how to operate successfully in various forms of partnerships. These knowledge resources known as firm’s source of competitive advantage because of its role as critical factors for the successful development and maintaining competitive advantage through creating value for the company’s stakeholder.Keywords: knowledge transfer, university-industry collaboration, key success factors, competitiveness